Potret Relasi Manusia dan Lingkungan dalam Novel Batu Berkaki Karya Chandra Bientang: Ekokritik Sastra - Khazimah Ila Salsabila; Sarwiji Suwandi (Simpati, 2026)
This study examines the representation of ecological values in Chandra Bientang’s novel Batu Berkaki through an ecocritical literary approach. The primary focus is to describe how the novel depicts the complex relationship between humans and the environment. The research method employs a descriptive qualitative approach using content analysis, grounded in Greg Garrard’s ecocritical framework, which encompasses the concepts of pollution, wilderness, apocalypse, dwelling, animals, and earth. Data were collected through close reading of the novel. The results show that the novel Batu Berkaki comprehensively represents all six of Garrard’s ecocritical concepts, highlighting the impact of human activities on the environment as well as the efforts of local communities to preserve ecological wisdom. This representation reaffirms the role of literature as a reflective medium for fostering ecological awareness and ethical relationships between humans and nature. This study contributes to the understanding of Indonesian literary ecocriticism, particularly in analyzing works that address environmental issues.